Prostatic Fluid Free Insulin-Like Growth Factor-1 in Relation to Benign Prostatic Hyperplasia:A Controlled Study - Ceylan, Cavit; Serel, Ahmet; Doluoglu, Omer Gokhan; Arma?an, Abdullah; Yüksel, Selcen (Urology Journal, 2014)
Abstract Purpose: Insulin-like growth factors (IGFs) have potent mitogenic and antiapoptotic effects on prostate tissue, whereas free IGF-1 is responsible for its metabolic effects but its role in benign prostatic hyperplasia (BPH) is unclear. Material and Methods: Plasma and prostatic fluid levels of free IGF-I were determined from the fasting bloods of 35 BPH cases admitted for treatment and 35 randomly selected population controls. Results: Prostatic fluid free IGF-1 concentrations did not differed significantly between two groups (P = .23). There was also no statistical difference in serum free IGF-1 levels between these groups. There was also no correlation between prostatic fluid free IGF-1 and serum prostate specific antigen (PSA) levels and prostate volume. When compared with control group, mean IPSS scores and prostate volumes of BPH group were significantly high, while mean maximum measured flow rate (Qmax) and international prostate symptom score (IPSS) and quality of life (QoL) scores were significantly low (P < .05). Conclusion: Our study shows that free IGF-I is not associated with BPH risk. Further investigation is needed to elucidate the role of the free IGF-1 in BPH.